Major F plasmid clusters are linked with ColV and pUTI89-like marker genes in bloodstream isolates of Escherichia coli - Cameron J. Reid; Max L. Cummins; Steven P. Djordjevic (BMC Genomics)
Abstract Background F plasmids are abundant in E. coli, carrying a variety of genetic cargo involved in fitness, pathogenicity, and antimicrobial resistance. ColV and pUTI89-like plasmids have drawn attention for their potential roles in various forms of extra-intestinal pathogenicity. However, the rates of their carriage and the overall diversity of F plasmids in E. coli bloodstream infections (BSI E. coli) remain unknown. Methods We performed a t-SNE-based cluster analysis of predicted F plasmids from a collection of 4711 BSI E. coli draft genomes to describe their diversity and abundance. We also screened them for markers of ColV and pUTI89-like plasmids, F plasmid replicon sequence types (RST) and E. coli sequence types (ST) to understand how genetic features were related to plasmid clusters. Results Predicted F plasmids in BSI E. coli draft genomes were embedded within five major clusters based on a model of complete F plasmid sequences. Nearly half of the clustered sequences belonged to two major clusters, which were associated with ColV and pUTI89-like marker genes, respectively. Genomes from the ColV cluster featured F2:A-:B1 and F24:A-B1 RSTs in association with ST95, ST58 and ST88, whilst the pUTI89-like cluster was mostly F29:A-:B10 linked to ST73, ST69, ST95 and ST131. Plasmids associated with different lineages of ST131 formed additional major clusters, whilst F51:A-:B10 plasmids in ST73 were also common. Conclusions ColV and pUTI89-like plasmid markers are predominant in BSI E. coli that carry F plasmids. These markers are associated with distinct clusters of plasmids across diverse sequence types of E. coli. We hypothesise that their abundance in BSI E. coli is partially driven by carriage of backbone genes previously shown to contribute to virulence in models of bloodstream infection. Their carriage by pandemic E. coli STs suggests clonal expansion also plays a role in their success in BSI. Ecological pathways via which these plasmids evolve, and spread are likely to be distinct as other studies show ColV is strongly associated with poultry and food animal production, whereas pUTI89-like plasmids appear to be mostly human-restricted.